Original paperFollow-up of patients with mycosis fungoides after interferon α2b treatment failure - Chmielowska, Ewa; Studziński, Maciej; Giebel, Sebastian; Krause, Anna; Olejniczak, Monika; Grzanka, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Treatment of T cell cutaneous lymphoma( CTCL) is a controversial subject and the effectiveness of treatment is still low. Aim: Report of single center experience of management CTCL after progression after first line treatment. Material and methods: We present 41 patients with CTCL, 29 received interferon α2b in first line, and 12 of them received second line therapy. Results: Overall response rate for second line therapy was 60%. Conclusions : Results of the follow-up of patients with mycosis fungoides after interferon 2b treatment failure with the literature review and discussion.